Impact of land use changes and global warming on extreme precipitation patterns in the Maritime Continent - Jie Hsu; Chao-An Chen; Chia-Wei Lan; Chun-Lien Chiang; Chun-Hung Li; Min-Hui Lo (npj Climate and Atmospheric Science)
Abstract Land use changes (LUC) and global warming (GW) significantly impact the Maritime Continent’s (MC) hydro-climate, but their effects on extreme precipitation events are underexplored. This study investigates the impacts of LUC and GW on wet and dry extremes in the MC using Community Earth System Model (CESM)simulations, analyzing 55 years for LUC and 200 years for GW. We find that LUC-induced deforestation increases surface warming, enhancing atmospheric instability and favoring local convection, leading to more frequent heavy precipitation. Meanwhile, GW amplifies the atmosphere’s water-holding capacity, further intensifying wet extremes. Our findings reveal a “wet-get-wetter, dry-get-drier” pattern driven by different mechanisms: dynamic processes primarily influence wet extremes under LUC, while changes in evapotranspiration control dry extremes. In contrast, under GW, wet extremes are driven by dynamic processes, while dry extremes are influenced by reduced moisture availability and weakened atmospheric circulation. This highlights the need for land management to address rising extreme risks.